An Analysis of Socio-Economic Growth of Coastal Society in Belitung Regency, Bangka Belitung Islands Province, Indonesia - Antomi, Yudi; Iskarni, Paus (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to analyze socio-economic growth rate of coastal society in Belitung Regency, Bangka Belitung Islands Province, Indonesia. The research was conducted through a secondary analysis, followed by focus group discussion (FGD), and processed using analytical techniques hierarchical process (AHP) with relevant government informants and community (stakeholders). Based on the results, the policy priorities are taken into consideration in the decision-making with respect to the vulnerability socioeconomic of coastal society in Belitung Regency. The five alternatives policy priorities are: (1) involving the coastal society in the tourism sector, (2) making ecotourism based trade center, (3) optimizing the use of the land seashores into economy sectors, (4) establishing informal institutions related to coastal society, and (5) establishing the formal institutions related to coastal area.